Dietary fiber and probiotics based on gut microbiota targeting for functional constipation in children with cerebral palsy - Huang, Congfu; Lyu, Jinli; Chu, Chunuo; Ge, Lan; Peng, Yuanping; Yang, Zhenyu; Xiong, Shenghua; Wu, Bin; Chen, Xiao; Zhang, Xiaowei (Frontiers in Pediatrics, 2022)
Gastrointestinal (GI) disorders are very common among children with cerebral palsy. Gut microbiota has been confirmed to maintain the normal GI physiological function and further contributed to the cerebral palsy through gut-brain axis. Our study was to investigate the effect of dietary fiber combined with probiotics on functional constipated children with cerebral palsy. In total, 35 patient children were enrolled and divided into general diet group (n=14) and liquid diet group (n=21). All the participates received Compound Dietary Fiber (CDF) for one month and lactic acid-producing and butyric acid-producing probiotics for six months. After one-month intervention, the frequency of spontaneous and manual defecation, and Bristol score were all significantly improved (P<0.001). The α-diversity of the gut microbiota was significantly increased after one-month intervention (P<0.05), with higher abundance of butyric acid-producing bacteria and lower abundance of opportunistic pathogen (P<0.05, FDR<0.05). However, impersistent effect of six-month intervention suggested insufficient impact of intaking probiotic alone and short duration of CDF intervention. Moreover, although the intervention had affected equally on constipation symptoms in cerebral palsy children with general diet and liquid diet, general diet group showed a greater and more durable change of gut microbiota and clinical phenotypes after intervention than liquid diet group, which indicated longer intervention time should be considered for liquid diet children. This study not only illustrated that supplementation of dietary fiber combined with probiotics can improve functional constipation in children with cerebral palsy, but also provide the guidance of optimal intervention strategy for the future studies, and will further benefit to the cerebral palsy children.